Branched polyolefin material modified hot melt adhesive and preparation method thereof
Through the modification of ethylene-vinyl acetate copolymer and branched polyolefin material, a composite hot melt adhesive polymer was synthesized, which solved the contradiction between the existing EVA hot melt adhesive in improving the body bonding and interface bonding properties, and achieved high wetting, high viscosity and high strength hot melt adhesive performance, which was especially suitable for high temperature environments.
Patent Information
- Application Number
- CN202411994582.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
There is a contradiction between the existing EVA hot melt adhesives improving the body bonding and interface bonding performance, and it is difficult to improve the performance of both.
Using ethylene-vinyl acetate copolymer as a matrix, a composite hot melt adhesive polymer is synthesized by modifying the branched polyolefin material, including ethylene-vinyl acetate copolymer, branched polyolefin-acrylate copolymer, branched polyolefin material, tackifying resin and viscosity regulator.
Through the hyperbranched structure and the long-chain characteristics of the terminal ester-based bond, the wetting, viscosity and bonding strength of the hot melt adhesive are improved, especially in high-temperature environments, which significantly improves the bonding strength and is suitable for high-temperature working environments.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot melt adhesives, and in particular relates to a branched polyolefin material modified hot melt adhesive and a preparation method thereof. Background Art
[0002] Ethylene-vinyl acetate (EVA) hot melt adhesive is a solvent-free, moisture-free, 100% solid fusible polymer. It is solid at room temperature and becomes a liquid adhesive that can flow and has a certain viscosity when heated and melted to a certain degree. EVA hot melt adhesive is the most widely used and largest-volume hot melt adhesive. When used, it only needs to be heated to a flowing state to complete the bonding. It has a fast curing speed and a simple and easy-to-control operation process. In addition, hot melt adhesive can also be processed into different shapes according to the use environment, and has a wide range of applications. It has hot glue relay for almost all materials, but the bonding strength is low. Its bonding behavior is that the melt infiltrates the surface of the adherend. After curing, it plays a bonding role through cohesion. The factors affecting its bonding performance are mainly cohesion and fluidity, which are regulated by the content of vinyl acetate (VA) segments. Increasing the VA content can increase the fluidity of the polymer, promote the wetting of the adherend surface, and enhance the interfacial bonding performance, but at the same time it will reduce the ethylene content, reduce the cohesion of the polymer, and weaken the bulk bonding performance. Therefore, simply using EVA as the base polymer and adjusting the ratio within a certain range can no longer meet the technical requirements of industrial development. Modification of EVA has become the main way to broaden its application areas, including grafting modification and multi-component blending modification of EVA polymers. Summary of the invention
[0003] In view of the above-mentioned deficiencies in the prior art, the present invention provides a composite hot melt adhesive polymer with ethylene-vinyl acetate copolymer as a matrix and modified by branched polyolefin material and a preparation method thereof, which can solve the contradiction between the existing methods in improving the bulk bonding and interface bonding performance.
[0004] The present invention adopts the following technical solution:
[0005] A branched polyolefin material modified hot melt adhesive comprises the following components in parts by weight:
[0006] 40-60 parts of ethylene-vinyl acetate copolymer
[0007] Branched polyolefin-acrylate copolymer 20-40 parts
[0008] 2-20 parts of branched polyolefin material
[0009] 5-30 parts of tackifying resin
[0010] 2 to 20 parts of viscosity modifier.
[0011] The branched polyolefin material modified hot melt adhesive may further include an antioxidant, the weight fraction of the antioxidant being
[0012] Antioxidant 0.1 to 3 parts.
[0013] The branched polyolefin-acrylate copolymer is prepared by polymerization of a bromine-containing branched polyolefin material and an acrylate monomer.
[0014] The acrylate monomer is methyl acrylate or 1,4-butanediol diacrylate.
[0015] The bromine-containing branched polyolefin material is one or more combinations of branched structural materials prepared by a solution polymerization method using ethylene or ethylene and C3-C5 olefins as the first monomer raw material and a bromine-containing monomer as the second monomer raw material. The bromine-containing branched polyolefin material is preferably a branched polymerization product of ethylene and a bromine-containing monomer.
[0016] The bromine-containing monomer is a brominated acrylamide compound or a brominated olefin compound, preferably 2-(2-bromoisobutyryl bromide)ethyl acrylate monomer (BIEA).
[0017] Further, the bromine-containing branched polyolefin material is prepared by the following method:
[0018] Ethylene gas, bromine-containing monomer, α-diimine palladium catalyst, and organic solvent A are stirred and reacted for 0.5 to 24 hours at a constant temperature of 10 to 30° C. and a constant ethylene pressure of 0.1 to 1 MPa. The obtained reaction mixture A is separated and purified to obtain a bromine-containing branched polyolefin material;
[0019] The organic solvent A is selected from one or more of dichloromethane, chlorobenzene, toluene, n-heptane, chloroform or petroleum ether, preferably dichloromethane.
[0020] The feed concentration of the bromine-containing monomer is 0.05-10.0 mol / L, preferably 0.1-3 mol / L; the addition amount of the α-diimine palladium catalyst is 0.5-50 g / L, preferably 2-20 g / L, based on the volume of the organic solvent A.
[0021] The branched polyolefin-acrylate copolymer is prepared from a bromine-containing branched polyolefin material and an acrylate monomer by the following method:
[0022] Under nitrogen protection, a bromine-containing branched polyolefin material, an acrylate monomer, an organic solvent B, pentamethyldiethylenetriamine or 2,2'-bipyridine as a ligand, and cuprous bromide as a catalyst are stirred and reacted at a temperature of 60 to 100° C. for 0.5 to 24 hours. The obtained reaction mixture B is separated and purified to obtain a branched polyolefin-acrylate copolymer.
[0023] The organic solvent B is selected from tetrahydrofuran, toluene or petroleum ether, preferably toluene.
[0024] The feeding concentration of the bromine-containing branched polyolefin material is 0.001-1 mol / L, and the molar ratio of the bromine-containing branched polyolefin material, the acrylate monomer, the ligand and the catalyst is 1:50-800:0.1-10:0.1-5.
[0025] Preferably, the cuprous bromide is pretreated before use. Under nitrogen protection, glacial acetic acid is added, and a "stirring-standing-taking out the supernatant" cycle operation is performed. After the supernatant becomes colorless and transparent, acetone solvent is added for washing, and the acetone is removed by vacuum treatment to obtain the final cuprous bromide.
[0026] The branched polyolefin material has a long and short branched chain structure, and is one or more combinations of branched structure materials prepared by a solution polymerization method using ethylene or ethylene and C3-C5 olefins as raw materials. The branched polyolefin material is preferably a single ethylene branched polymerization product. The appearance of the branched polyolefin material can be elastomer, rubber, oil or wax.
[0027] Furthermore, the branched polyolefin material preferably has a weight average molecular weight of 800 to 500,000 g / mol, a branching degree of 50 to 220 / 1000C, and a crystallinity of 0 to 20% (preferably 0.1 to 15%). The branched polyolefin material has a melt index of 0.01 to 20 g / 10 min, preferably 0.5 to 15 g / 10 min, at 190°C and a load of 2.16 kg.
[0028] Furthermore, the weight average molecular weight of the branched polyolefin material is preferably 8000 to 50000 g / mol, and the degree of branching is 55 to 120 / 1000C.
[0029] Furthermore, the branched polyolefin material has a melting point of 10°C to 90°C, preferably 20°C to 80°C.
[0030] In the present invention, the branched polyolefin elastomer can be prepared by the following method:
[0031] Add an organic solvent, a catalyst and a co-catalyst into a reactor, control the temperature at 10 to 100° C., introduce ethylene into the reactor to carry out a polymerization reaction, the ethylene pressure is 0.1 to 5 MPa, the reaction time is 10 to 90 min, after the reaction is completed, add the reaction solution into acidified ethanol to terminate the reaction to obtain a solid precipitate, wash and dry the solid precipitate to obtain a branched polyolefin elastomer;
[0032] The catalyst is a late transition metal catalyst.
[0033] The late transition metal catalyst is a metal complex olefin polymerization catalyst with a late transition metal atom such as nickel (II), palladium (II), iron (II), cobalt (II), ruthenium (II) as the active center, and the chelating ligand is selected from the types of N^N, P^N, N^O, P^O, etc. All kinds of late transition metal catalysts disclosed in the prior art that can catalyze ethylene polymerization to prepare branched polyolefins and can obtain the defined parameters of the branched polyolefin material of the present invention can be applied to the present invention.
[0034] Furthermore, the late transition metal catalyst is a Brookhart catalyst, such as a (a-diimine) nickel / palladium complex, and more preferably an α-diimine nickel catalyst.
[0035] The cocatalyst is one or more of diethylaluminum monochloride, ethylaluminum dichloride, methylaluminoxane, polymethylaluminoxane, and ethylaluminum sesquichloride (EASC), preferably diethylaluminum monochloride.
[0036] The molar ratio of Al in the co-catalyst to Ni in the α-diimine nickel catalyst is 50 to 1000:1.
[0037] The polymerization reaction is carried out in an organic solvent, and the organic solvent is one or more of dichloromethane, toluene and n-hexane.
[0038] In the present invention, a branched structure with adjustable length and short branched chain structures is obtained by long chain branching polymerization in a solution using a late transition metal catalyst. Since the present invention is an in-situ polymerization of ethylene, the branched chain contains long chains and short chains, has a high degree of branching, and the long branched chain increases the crosslinking point, has a low crystallinity, and improves the performance of the elastomer.
[0039] In the present invention, the content of VA in the ethylene-vinyl acetate copolymer is 12 to 33 mol%, preferably 15 to 30%.
[0040] In the present invention, the ratio of the mass of the branched polyolefin material to the total mass of the ethylene-vinyl acetate copolymer and the branched polyolefin-acrylate copolymer is preferably 2.5% or more. The ratio of the mass of the branched polyolefin-acrylate copolymer to the total mass of the ethylene-vinyl acetate copolymer and the branched polyolefin-acrylate copolymer is preferably 40% or more.
[0041] In the present invention, the tackifying resin is one or more of C5 petroleum resin, C9 petroleum resin, DCPD petroleum resin and terpene resin.
[0042] The viscosity modifier is one or more of paraffin wax, microcrystalline wax, dicyclopentadiene, polyethylene wax, polypropylene wax, and rosin resin, preferably microcrystalline wax.
[0043] The antioxidant is any one of phenolic and phosphite antioxidants or a mixture of two of them.
[0044] The present invention also provides a method for preparing the branched polyolefin material modified hot melt adhesive, the method comprising:
[0045] The raw materials are mixed evenly according to the formula ratio and then added into a twin-screw extruder, and melt-extruded at a temperature of 150-230° C. to obtain the branched polyolefin material modified hot melt adhesive.
[0046] The present invention has the following beneficial effects:
[0047] The invention designs and synthesizes a polyethylene-acrylate multi-polymer with a high degree of branching and containing different terminal ester chain lengths in the structure, and utilizes the synergistic effect of the unique three-dimensional dendritic structure characteristics of the hyperbranching and the ester terminal chain length to improve the fluidity of the polymer melt, enhance the wettability of the adherend surface, and achieve the improvement of the interfacial bonding strength. At the same time, after curing, the cohesion at the ethylene chain segment of the EVA is not destroyed, and the bulk bonding strength is guaranteed. In addition, the ester terminal of the copolymer has good compatibility with the vinyl acetate molecular chain, which promotes the hyperbranched copolymer to form a good dispersion in the system.
[0048] The branched polyolefin material designed and synthesized by the present invention has a high degree of branching and contains long and short branches in the molecular structure, which plays the role of adjusting viscosity, enhancing adhesion and tensile strength, and improving flexibility and temperature resistance in the composite system.
[0049] Compared with common EVA hot melt adhesive, the hot melt adhesive modified by the branched polyolefin material of the present invention has improved wettability, viscosity and bonding strength by taking advantage of the hyperbranched structure of the copolymer and the long-chain characteristics of the terminal ester group. It has good bonding performance for metals, plastics, composite materials, etc., and the shear strength and peel strength are significantly improved, especially the heat resistance is significantly improved. After high-temperature treatment, the bonding strength is significantly improved compared with the existing hot melt adhesive, and it is suitable for high-temperature working environment. DETAILED DESCRIPTION
[0050] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the implementation methods of the present invention are not limited thereto.
[0051] The acrylic acid ester monomer in the embodiment is selected from methyl acrylate;
[0052] The bromine-containing monomer in the embodiment is 2-(2-bromoisobutyryl bromide)ethyl acrylate (BIEA), and the structural formula is as follows:
[0053]
[0054] In the embodiment, organic solvent A is dichloromethane, and organic solvent B is toluene;
[0055] The ligand in the embodiment is pentamethyldiethylenetriamine.
[0056] The α-diimine palladium catalyst can be one of the following, and can be synthesized according to the public literature: The α-diimine palladium catalyst 1 is used in this embodiment.
[0057]
[0058] Embodiment 1:
[0059] (1) Under ethylene protection, 2.12 g of bromine-containing monomer BIEA, 0.2 g of catalyst α-diimine palladium catalyst 1 and 20 ml of anhydrous grade dichloromethane were added to a 50 ml Schlenk reaction bottle, and the reaction was stirred for 24 h at a constant temperature of 25° C. and a constant ethylene pressure of 0.1 MPa. After the reaction was completed, the dichloromethane solvent was blown away with cold wind, 15 ml of tetrahydrofuran was added to dissolve the above product, 5 to 8 drops of hydrogen peroxide and hydrochloric acid were added, and the mixture was stirred for 12 h to dissolve the palladium particles. The mixed solution was filtered with a 0.22 μm filter membrane and then the solvent was blown away with cold wind. The obtained polymer product was dissolved in 10 ml of tetrahydrofuran again, and 50 ml of methanol was added to precipitate the polymer. The upper layer of the solution was removed, and the obtained polymer product was vacuum dried at 60° C. for 24 h to obtain 3.1 g of bromine-containing branched polyolefin material.
[0060] (2) Pretreatment of cuprous bromide: adding glacial acetic acid under nitrogen protection, and carrying out a "stirring-standing-taking out the supernatant" cycle operation until the supernatant becomes colorless and transparent, adding acetone solvent for washing, and vacuuming to remove the acetone to obtain the final cuprous bromide.
[0061] (3) Under nitrogen protection, 0.6 g of bromine-containing branched polyolefin material (feed concentration 0.03 mol / L), 10 g of methyl acrylate (0.116 mol), 10 ml of anhydrous toluene and 0.26 g of ligand pentamethyldiethylenetriamine (1.5 mmol) were added to a 100 ml Schlenk reaction bottle, and the "liquid nitrogen freezing-vacuuming-thawing" cycle operation was performed three times. Then, 0.14 g of cuprous bromide (1 mmol) was added under nitrogen protection, and the mixture was stirred at a constant temperature of 80° C. for 24 h. After the polymerization was completed, the solvent was removed by cold air blowing. The obtained preliminary polymerization product was dissolved in 10 ml of tetrahydrofuran, and solid impurities such as copper salt were removed by centrifugation (4000 rpm, 10 min). The supernatant was removed, and 180 ml of methanol and 20 ml of deionized water were added to precipitate the polymerization product. The polymerization product was obtained after removing the supernatant. The obtained product was vacuum dried at 60° C. for 24 h to obtain a branched polyolefin-acrylate copolymer, which was recorded as copolymer A.
[0062] Embodiment 2:
[0063] (1) Same as the first step in Example 1;
[0064] (2) Same as the second step in Example 1;
[0065] (3) Under nitrogen protection, 0.6 g of bromine-containing hyperbranched polyethylene copolymer, 20 g of methyl acrylate, 10 ml of anhydrous toluene and 0.26 g of ligand pentamethyldiethylenetriamine were added to a 100 ml Schlenk reaction bottle, and a "liquid nitrogen freezing-vacuuming-thawing" cycle operation was performed three times. Then, 0.14 g of cuprous bromide was added under nitrogen protection, and the mixture was stirred at a constant temperature of 80° C. for 24 h. After the polymerization was completed, the solvent was removed by blowing cold air. The obtained preliminary polymerization product was dissolved in 10 ml of tetrahydrofuran, and solid impurities such as copper salt were removed by centrifugation (4000 rpm, 10 min). The supernatant was removed, and 180 ml of methanol and 20 ml of deionized water were added to precipitate the polymerization product. The polymerization product was obtained after removing the supernatant. The obtained product was vacuum dried at 60° C. for 24 h to obtain an ester-containing hyperbranched polyethylene copolymer, which was recorded as copolymer B.
[0066] Embodiment 3:
[0067] (1) Same as the first step in Example 1;
[0068] (2) Same as the second step in Example 1;
[0069] (3) Under nitrogen protection, 0.6 g of bromine-containing hyperbranched polyethylene copolymer, 30 g of methyl acrylate, 10 ml of anhydrous toluene and 0.26 g of ligand pentamethyldiethylenetriamine were added to a 100 ml Schlenk reaction bottle, and a "liquid nitrogen freezing-vacuuming-thawing" cycle operation was performed three times. Then, 0.14 g of cuprous bromide was added under nitrogen protection, and the mixture was stirred at a constant temperature of 80° C. for 24 h. After the polymerization was completed, the solvent was removed by blowing cold air. The obtained preliminary polymerization product was dissolved in 10 ml of tetrahydrofuran, and solid impurities such as copper salt were removed by centrifugation (4000 rpm, 10 min). The supernatant was removed, and 180 ml of methanol and 20 ml of deionized water were added to precipitate the polymerization product. The polymerization product was obtained after removing the supernatant. The obtained product was vacuum dried at 60° C. for 24 h to obtain an ester-containing hyperbranched polyethylene copolymer, which was recorded as copolymer C.
[0070] Example 4
[0071] In 100 mL of n-hexane solvent, α-diimine nickel catalyst (2 μmol) and sesquiethylaluminum chloride (2 mmol, Al:Ni molar ratio=1000) were added, the temperature was controlled at 20-80° C., ethylene was introduced to carry out polymerization reaction, timing was started after the ethylene pressure was stable, the ethylene pressure was 0.1-5 MPa, the reaction time was 10-70 min, after the reaction was completed, the reaction solution was added to 200 mL of acidified ethanol, stirred for 10 h, filtered, washed with ethanol, and vacuum dried to obtain a branched polyolefin material;
[0072] The α-diimine nickel catalyst used in this embodiment is prepared according to the following reaction formula:
[0073]
[0074] In the formula I, R1 is phenyl or substituted phenyl, and the substituted phenyl is p-aminophenyl, p-methylphenyl, p-methoxyphenyl or p-tert-butylphenyl;
[0075] R2 is phenyl or substituted phenyl, wherein the substituted phenyl is p-methylphenyl, p-methoxyphenyl, p-fluorophenyl or p-tert-butylphenyl;
[0076] R3 is phenyl or substituted phenyl, wherein the substituted phenyl is p-methoxyphenyl, p-fluorophenyl or p-tert-butylphenyl;
[0077] In a toluene solvent, the aniline compound represented by formula II and diacetyl are mixed in a molar ratio of 2 to 2.2:1, and heated to 60 to 90°C for reaction for 20 to 24 hours under the action of a catalytic amount of p-toluenesulfonic acid. Then, the mixture is separated by water using a water separator and refluxed for 2 to 3 days to obtain a diimine ligand compound represented by formula III;
[0078] The diimine ligand compound shown in formula III and (DME)NiBr2 are mixed in a molar ratio of 1:0.5-2, dissolved in dichloroethane solvent, and stirred for reaction for 10-24 hours under nitrogen protection to obtain an α-diimine nickel catalyst shown in formula I.
[0079] In this embodiment, the α-diimine nickel catalyst in which R1, R2 and R3 are all p-tert-butylphenyl is prepared by the following specific method:
[0080] 2,4-di(p-tert-butylphenyl)-6-di-p-tert-butylphenyl methylaniline (4mmol) and diacetyl (2mmol) were dissolved in 100mL toluene, and 10mg of p-toluenesulfonic acid (PTSA) was added, and the mixture was stirred and refluxed at 80°C for 24h. Then, the mixture was refluxed for 3 days using a Deanstark water separator. After the reaction solution was cooled to room temperature, part of the solvent was evaporated under reduced pressure to precipitate a solid. 400mL of methanol was added to precipitate a solid product, which was filtered, and the filter cake was washed with methanol and dried to obtain a diimine ligand compound with a yield of 81%.
[0081] Under nitrogen protection, the diimine ligand compound and (DME)NiBr2 (0.2 mmol) and the diimine ligand compound (0.20 mmol) were mixed and dissolved in 5 mL of dichloromethane, stirred and reacted at room temperature for 20 hours, and dichloromethane was removed under reduced pressure and ether was added to precipitate a red solid, which was filtered, washed with ether, and dried to obtain an α-diimine nickel catalyst. The yield was about 85%
[0082] In 100 mL of n-hexane solvent, α-diimine nickel catalyst (2 μmol) and diethylaluminum monochloride (2 mmol, Al:Ni molar ratio=1000) were added, the temperature was controlled at 20-80° C., ethylene was introduced to carry out polymerization reaction, timing was started after the ethylene pressure was stable, the ethylene pressure was 0.1-5 MPa, the reaction time was 10-70 min, after the reaction was completed, the reaction solution was added to 200 mL of acidified ethanol, stirred for 10 h, filtered, washed with ethanol, and vacuum dried to obtain a branched polyolefin elastomer;
[0083] Using ethylene as raw material, hexane as solvent, α-diimine nickel catalyst as catalyst, and diethylaluminum monochloride as co-catalyst, a branched polyolefin material D (reaction temperature 45°C, pressure 0.1MPa, melt index 8g / 10min, branching degree 76 / 1000C, molecular weight 16000g / mol, crystallinity 2%) was prepared by solution polymerization. Copolymers A, B, and C were blended with EVA (VA content 25%) and branched polyolefin material D respectively to prepare hot melt adhesives. The specific steps are as follows:
[0084] According to the formula in Table 1, the raw materials were mixed with a high-speed mixer, added into a twin-screw extruder, and melt-extruded at 180° C. to obtain a solid hot melt adhesive.
[0085] In this embodiment, the tackifying resin is C5 petroleum resin, the viscosity modifier is microcrystalline wax, and the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 3:2.
[0086] Table 1 Mass fraction of each component of hot melt adhesive in experiments 1 to 4
[0087]
[0088] The hot melt adhesives obtained in Experiments 1 to 4 were tested for their bonding properties, and the results are shown in Table 2.
[0089] Shear strength: tested according to GB7124-1986.
[0090] 180° peel strength: tested according to GB / T2790-1995.
[0091] High temperature resistance: Place at 95±2℃ for 6 hours, then perform shear strength test or 180° peel strength test after reaching room temperature.
[0092] Table 2 Performance test results
[0093] Experiment 1 Experiment 2 Experiment 3 Experiment 4 Experiment 5 Experiment 6 Shear strength (MPa) glass 9.3 9.1 8.5 5.5 6.1 3.4 Shear strength (MPa) steel 8.5 8.8 8.9 5.9 5.7 3.2 Shear strength (MPa) PC 8.8 9.2 8.7 4.8 5.2 2.8 Peel strength (N / cm) glue-glass 215 218 213 185 188 181 Peel strength (N / cm) Adhesive-back sheet 214 215 212 180 181 175 Shear strength after high temperature (MPa) steel 7.8 6.5 6.9 3.3 3.6 1.8 Peel strength after high temperature (N / cm) Adhesive-back sheet 210 211 207 167 170 158
[0094] The results in Table 2 show that the shear strength of pure EVA hot melt adhesive is low and its high temperature resistance is reduced. Since EVA has a low melting point, its bonding performance decreases after high temperature treatment.
[0095] After modification with branched polyolefin-acrylate copolymer and branched polyolefin materials respectively, the shear strength and peel strength are improved, and the branched polyolefin material has a more obvious improvement in high temperature performance. However, after modification with both, the shear strength and peel strength are significantly improved, especially after high temperature treatment, the shear strength and peel strength do not decrease significantly, and are significantly improved compared to pure EVA hot melt adhesive.
[0096] Example 5
[0097] Copolymer A, branched polyolefin D and EVA (VA content 25%) were blended in different mass ratios to prepare hot melt adhesives. Other reaction materials and reaction steps were the same as those in Example 4. The formula is shown in Table 3. The performance test results are shown in Table 4.
[0098] Table 3 Mass fraction of each component of hot melt adhesive in experiments 5 to 7
[0099] Experiment 7 Experiment 8 Experiment 9 Experiment 10 EVA 40 60 90 60 Copolymer A 40 40 10 40 Branched Polyolefin D 2 2 2 8 C5 Petroleum Resin 15 15 15 15 Microcrystalline wax 10 10 10 10 Antioxidants 0.5 0.5 0.5 0.5
[0100] Table 4 Performance test results
[0101] Experiment 7 Experiment 8 Experiment 9 Experiment 10 Shear strength (MPa) glass 9.0 8.8 5.3 9.2 Shear strength (MPa) steel 8.3 8.3 5.8 8.5 Shear strength (MPa) PC 8.4 8.5 4.5 8.8 Peel strength (N / cm) glue-glass 213 212 183 216 Peel strength (N / cm) Adhesive-back sheet 210 210 180 215 Shear strength after high temperature (MPa) steel 7.5 7.3 3.3 8.1 Peel strength after high temperature (N / cm) Adhesive-back sheet 207 202 168 212
[0102] The results in Table 4 show that the amount of copolymer A added in Experiment 9 is relatively small, only 10 parts, and the bonding performance is poor. The amount of branched polyolefin D used in Experiment 8 is relatively small, and the shear strength and peel strength are reduced compared with Experiment 1, especially the peel strength after high temperature. However, it can also meet the requirements. The amount of branched polyolefin D is increased in Experiment 10, and the viscosity does not change significantly after high temperature treatment.
[0103] In Experiment 7, the relative content of copolymer A is increased, and the relative amount of branched polyolefin D is also increased compared with Experiment 8, so the high temperature bonding performance is improved.
[0104] In the present invention, the ratio of the mass of the branched polyolefin material to the total mass of EVA and the branched polyolefin-acrylate copolymer is preferably above 2.5%. The ratio of the mass of the branched polyolefin-acrylate copolymer to the total mass of EVA and the branched polyolefin-acrylate copolymer is preferably above 40%.
[0105] Example 6
[0106] Copolymer A was blended with EVA with different VA contents to prepare hot melt adhesive. Experiment 11 used EVA with a VA content of 15%, and Experiment 12 used EVA with a VA content of 30%. Other reaction raw materials and reaction steps were the same as Experiment 1 in Example 4. The performance test results are shown in Table 5.
[0107] Table 5 Performance test results
[0108] Experiment 11 Experiment 12 Shear strength (MPa) glass 9.5 7.6 Shear strength (MPa) steel 9.6 7.3 Shear strength (MPa) PC 9.2 6.9 Peel strength (N / cm) glue-glass 213 221 Peel strength (N / cm) Adhesive-back sheet 212 219 Shear strength after high temperature (MPa) steel 6.9 6.4 Peel strength after high temperature (N / cm) Adhesive-back sheet 207 216
[0109] Generally speaking, as the VA content increases, the shear strength of the hot melt adhesive decreases and the peel strength increases. However, after adding copolymer A and branched polyolefin materials, the shear strength of the high VA content EVA in Experiment 12 is significantly improved, which may be related to the enhanced cohesion of the hot melt adhesive. After the VA content in Experiment 12 increases, the performance of the glass after high temperature is the best, but the shear strength is not as good as that in Experiment 1.
[0110] From the above detailed description of the embodiments of the present invention, it can be understood that the present invention provides a key polymer for high-end hot melt adhesive and a preparation method thereof, which can utilize its unique three-dimensional dendritic structure characteristics of hyperbranching and the synergistic effect of the terminal ester chain length and branched polyolefin materials to improve the fluidity of the polymer melt and achieve improved interface bonding strength. At the same time, after curing, the cohesion at the ethylene segment is not destroyed, the bulk bonding strength is guaranteed, and a series of composite hot melt adhesive polymer products with high wettability, high viscosity and high strength are obtained to solve the contradiction between the existing methods in improving the bulk bonding and interface bonding performance, and break through the barriers of bonding performance.
[0111] Although the preferred implementation of the present invention has been disclosed as above, it does not limit the present invention. Any technician in this field can make appropriate improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the claims.
Claims
1. A branched polyolefin modified hot melt adhesive, characterized in that The branched polyolefin material modified hot melt adhesive comprises the following components in parts by weight: 40-60 parts of ethylene-vinyl acetate copolymer Branched polyolefin-acrylate copolymer 20-40 parts 2-20 parts of branched polyolefin material 5-30 parts of tackifying resin 2 to 20 parts of viscosity modifier; The branched polyolefin-acrylate copolymer is prepared by polymerization of a bromine-containing branched polyolefin material and an acrylate monomer; The bromine-containing branched polyolefin material is one or more combinations of branched structure materials prepared by a solution polymerization method using ethylene or ethylene and C3-C5 olefins as the first monomer raw material and a bromine-containing monomer as the second monomer raw material; The branched polyolefin material has a long and short branched chain structure and is one or more combinations of branched structure materials prepared by a solution polymerization method using ethylene or ethylene and C3-C5 olefins as raw materials; the branched polyolefin material has a weight average molecular weight of 800-500000 g / mol, a branching degree of 50-220 / 1000C, and a crystallinity of 0-20%.
2. The branched polyolefin modified hot melt adhesive according to claim 1, characterized in that The bromine-containing branched polyolefin material is a branched polymerization product of ethylene and a bromine-containing monomer; the branched polyolefin material is a single ethylene branched polymerization product.
3. The branched polyolefin modified hot melt adhesive according to claim 1, characterized in that The acrylate monomer is methyl acrylate or 1,4-butanediol diacrylate; The bromine-containing monomer is a brominated acrylamide compound or a brominated olefin compound.
4. The branched polyolefin modified hot melt adhesive according to claim 1, characterized in that The bromine-containing branched polyolefin material is prepared by the following method: Ethylene gas, bromine-containing monomer, α-diimine palladium catalyst, and organic solvent A are stirred and reacted for 0.5 to 24 hours at a constant temperature of 10 to 30° C. and a constant ethylene pressure of 0.1 to 1 MPa. The obtained reaction mixture A is separated and purified to obtain a bromine-containing branched polyolefin material; The organic solvent A is selected from one or more of dichloromethane, chlorobenzene, toluene, n-heptane, chloroform or petroleum ether.
5. The branched polyolefin modified hot melt adhesive according to claim 4, characterized in that The branched polyolefin-acrylate copolymer is prepared from a bromine-containing branched polyolefin material and an acrylate monomer by the following method: Under nitrogen protection, a bromine-containing branched polyolefin material, an acrylate monomer, an organic solvent B, pentamethyldiethylenetriamine or 2,2'-bipyridine as a ligand, and cuprous bromide as a catalyst are stirred and reacted at a temperature of 60 to 100° C. for 0.5 to 24 hours. The obtained reaction mixture B is separated and purified to obtain a branched polyolefin-acrylate copolymer.
6. The branched polyolefin modified hot melt adhesive according to claim 1, characterized in that The branched polyolefin material modified hot melt adhesive also includes an antioxidant, the weight fraction of the antioxidant is Antioxidant 0.1 to 3 parts.
7. The branched polyolefin modified hot melt adhesive according to claim 1, characterized in that The content of VA in the ethylene-vinyl acetate copolymer is 12-33 mol%.
8. The branched polyolefin modified hot melt adhesive according to claim 1, characterized in that The tackifying resin is one or more of C5 petroleum resin, C9 petroleum resin, DCPD petroleum resin, and terpene resin; The viscosity modifier is one or more of paraffin wax, microcrystalline wax, dicyclopentadiene, polyethylene wax, polypropylene wax, and rosin resin.
9. The branched polyolefin modified hot melt adhesive according to claim 1, characterized in that The branched polyolefin material is prepared by the following method: Add an organic solvent, a catalyst and a co-catalyst into a reactor, control the temperature at 10-100° C., introduce ethylene into the reactor to carry out a polymerization reaction, the ethylene pressure is 0.1-5 MPa, the reaction time is 10-90 min, after the reaction is completed, add the reaction solution into acidified ethanol to terminate the reaction to obtain a solid precipitate, wash and dry the solid precipitate to obtain a branched polyolefin material; The catalyst is a late transition metal catalyst.
10. The method for preparing the branched polyolefin material modified hot melt adhesive according to any one of claims 1 to 9, characterized in that The method is: The raw materials are mixed evenly according to the formula ratio and then added into a twin-screw extruder, and melt-extruded at a temperature of 150-230° C. to obtain the branched polyolefin material modified hot melt adhesive.
Citation Information
Cited By
High-temperature-resistant hot-melt pressure-sensitive adhesive and preparation method thereof
CN120310486A
High-salt-tolerance zwitterionic synthetic thickening agent and application thereof in digital printing paste
CN121021777A